Manuel Gutiérrez Nájera's "La novela del tranvía" (1882) and the Literature of Urban Transit. Issue 4 (2nd October 2018) - Amann, Elizabeth
Abstract: This essay considers Manuel Gutiérrez Nájera's "La novela del tranvía" (1882) in light of the literature of collective urban transportation in the nineteenth century. The first part of the study explores how the Mexican text represents the tram and how its narrator-passenger attempts to deal with the vastness and unfamiliarity of the urban space by projecting clichés and commonplaces onto his fellow travelers. The second part compares and contrasts the work with Benito Pérez Galdós's short story "La novela en el tranvía" (1871), which similarly features a narrator who projects plots onto other tram passengers. The essay concludes with some reflections on the esthetic classification of the Mexican work.